The History of Anatomy, its importance and new trends in the teaching/learning process - Letícia Iega Santana; Daniela Vieira Buchaim; Abdul Latif Hamzé; Carlos Henrique Bertoni Reis; Cleuber Rodrigo de Souza Bueno; Miguel Ângelo de Marchi; Karina Torres Pomini; Rogério Leone Buchaim (Archives of Anatomy and Physiology - Peertechz Publications, 2022)
Anatomy, in its broadest concept, is the science that studies the development and constitution of living beings. The study of human anatomy becomes mandatory for all courses in the Health Area since its understanding is fundamental for understanding the physiology and pathological processes that affect the human being. Some strategies such as Youtube videos, digital tables such as Anatomage, synthetic pieces and body painting were created to facilitate and socialize access to such information. The main objective of this short communication was to integrate the knowledge obtained through the survey of the History of Anatomy with the current trends of new teaching methodologies, which can help in learning but cannot replace the use of natural parts such as corpses.